Significance of Liver Size in Hepatic Surgery. Issue 4 (1997) - Yanaga, K.; Honda, H.; Ikeda, Y.; Nishizaki, A. T.; Yamamoto, K.; Sugimachi, K.
Abstract : The purpose of this study was to evaluate the significance of liver volumetry as a parameter for hepatic functional reserve in cirrhotic patients with hepatocellular carcinoma. Liver volume was calculated from preoperative computed tomograms of 44 cirrhotic patients who underwent elective hepatic resections for hepatocellular carcinoma. The liver volume per body weight of non-alcoholic cirrhotics was significantly smaller than that of alcoholic cirrhotics (20.9 vs. 26.7 cc/kg; p=0.03). The values for alcoholic cirrhotics was comparable with normal values. The liver volume per body weight of the cirrhotic patients demonstrated correlation with the preoperative serum albumin (p<0.01) and indocyanine green clearance (p=0.02). We conclude that the determination of hepatic atrophy by volume try can serve as a parameter for the assessment of hepatic reserve but not as a predictor of postoperative complications in elective liver surgery for cirrhotic patients.